Detecting Nothofagus pumilio Growth Reductions Induced by Past Spring Frosts at the Northern Patagonian Andes - Sangüesa-Barreda, Gabriel; Villalba, Ricardo; Rozas, Vicente; Christie, Duncan A.; Olano, José Miguel (Frontiers in Plant Science, 2019)
Extreme climatic events such as late frosts in spring during leaf flush, have considerable impacts on the radial growth of temperate broadleaf trees. Albeit, all broadleaved species are potentially vulnerable, damage depends on the particularities of the local climate, the species and its phenology. The impact of late spring frosts has been widely investigated in the Northern Hemisphere, but the potential incidence in Southern Hemisphere tree species is still poorly known. Here, we reconstruct spring frost occurrence at 30 stands of the deciduous tree Nothofagus pumilio in its northern range of distribution in the Patagonian Andes. We identified tree ring-width reductions at stand level not associated with regional or local drought events, matching unusual minimum spring temperatures during leaf unfolding. Several spring frosts were identified along the northern distribution of N. pumilio, being more frequent in the more continental Argentinean forests. Spring frost in 1980 had the largest spatial extent. The spring frosts in 1980 and 1992 also induced damages in regional orchards. Spring frost damage was associated with (i) a period of unusually warm temperatures at the beginning of leaf unfolding, followed by (ii) freezing temperatures. This study helps expand our understanding of the climatic constraints that could determine the future growth and dynamics of Andean deciduous forests and the potential use of tree-rings as archives of extreme events of spring frosts in northern Patagonia.